2017
DOI: 10.1080/21551197.2017.1280868
|View full text |Cite
|
Sign up to set email alerts
|

Food Label Knowledge, Usage and Attitudes of Older Adults

Abstract: Few recent studies have investigated food label practices in older adults. This cross-sectional study surveyed adults, 60 years and older in Delaware (n = 100, 82% female, 74% between 60 and 79 years, 49% Caucasian, 45% African Americans) to examine associations between food label knowledge, attitudes, and usage patterns. A 28-item questionnaire assessed knowledge, attitudes, usage, and demographic information. Bivariate analysis results showed food label knowledge was associated with education and monthly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…Those who were women, employed, food secure, younger, more educated, higher income or of White race/ethnicity were more likely to report awareness of MyPlate or MyPyramid. These results are consistent with previous research showing that female sex, higher socio-economic status and higher educational attainment are the factors associated with nutrition-related knowledge, as measured by validated assessment (15,20,49) . Those more likely to report use of nutrition information were also younger, women, college-educated and of higher socio-economic status.…”
Section: Discussionsupporting
confidence: 93%
“…Those who were women, employed, food secure, younger, more educated, higher income or of White race/ethnicity were more likely to report awareness of MyPlate or MyPyramid. These results are consistent with previous research showing that female sex, higher socio-economic status and higher educational attainment are the factors associated with nutrition-related knowledge, as measured by validated assessment (15,20,49) . Those more likely to report use of nutrition information were also younger, women, college-educated and of higher socio-economic status.…”
Section: Discussionsupporting
confidence: 93%
“…This might occur because women were more expected to comply with the efficiency of nutrition data on food labels and generally had more concerns in health and nutrition topics in comparison to men (39). In contrast to findings from the current study, a study by Jackey et al in Delaware, USA (8), showed that food label awareness was associated with monthly income. In another study by Miller et al (40) in California, USA, 2013-2014, accuracy and attention to food labels decreased with increasing age.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have been carried out on knowledge and attitude of various populations about food labeling in various regions of the world. In a cross-sectional study by Jackey et al (8), less than half of 60-year-old adults and those older in Delaware, USA, were able to interpret food label information correctly. Viola et al (9) assessed knowledge and understanding of food labels in young adults mostly with higher education levels through an on-line survey and showed that they were generally able to identify healthier food products based on nutritional label information.…”
Section: Introductionmentioning
confidence: 97%
“…Table 5 shows that higher age (r=0.272; p<0.001) and income (r=0.165; p=0.001) of subjects was associated with better knowledge of nutrition labels. Similar results were found in Jackey et al (2017) and Cannoosamy et al (2014). This implies that older and wealthier subjects are more likely to be exposed to health or nutrition-related news.…”
Section: Knowledge On Food and Nutrition Labelsupporting
confidence: 79%